BIRD MIGRATION - Saxena, V.S. (SCHOOL SCIENCE, 2012)
After more than 2,000 years of observations climaxed by a century of experimental studies, we are still not certain regarding many facets of migration. We have authentic data on breeding range, wintering quarters and many migratory routes of a large number of birds but we still are not in a definite stage to explain why birds go where they do at the time they do, and their manner of navigation is only partially understood.